IMPLEMENTASI SERTIFIKASI HALAL OLEH LPPOM MUI SUMATERA UTARA TAHUN 2024 - Sulidar, Sulidar; Hafiz Fahrurrozi Tanjung; M. Aldi; Saputra Ramadhan; Syaripa Hanum Ritonga; Jihan tuffahati Nasution (JSE: Jurnal Sharia Economica, 2025)
This study aims to examine the implementation of halal certification by the Assessment Institute for Foods, Drugs and Cosmetics of the Indonesian Ulema Council (LPPOM MUI) in North Sumatra in 2024. A descriptive qualitative method with a case study approach was employed, utilizing in-depth interviews, participatory observation, and document analysis. The findings reveal that the certification process follows national regulations through the SIHALAL platform, encompassing stages of registration, document verification, field audit, and fatwa deliberation. The primary challenges identified include incomplete documentation from business actors, limited digital literacy among MSMEs, and dynamic regulatory changes. LPPOM MUI addresses these issues through on-site outreach, personalized assistance, and collaboration with universities and local governments. The study also found a significant increase in public trust toward halal labels after the formal legal mandate and the implementation of criminal sanctions for violations. LPPOM MUI demonstrates institutional commitment through document validation, adherence to auditor ethics, and transparent certification costs. These findings contribute to strengthening the national halal assurance system and suggest the need to enhance MSME capacity in utilizing halal certification as an economic value proposition.